10x-5-4x-3+2=0

Simple and best practice solution for 10x-5-4x-3+2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-5-4x-3+2=0 equation:


Simplifying
10x + -5 + -4x + -3 + 2 = 0

Reorder the terms:
-5 + -3 + 2 + 10x + -4x = 0

Combine like terms: -5 + -3 = -8
-8 + 2 + 10x + -4x = 0

Combine like terms: -8 + 2 = -6
-6 + 10x + -4x = 0

Combine like terms: 10x + -4x = 6x
-6 + 6x = 0

Solving
-6 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 6x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 6x = 0 + 6
6x = 0 + 6

Combine like terms: 0 + 6 = 6
6x = 6

Divide each side by '6'.
x = 1

Simplifying
x = 1

See similar equations:

| -6=3(3x-5) | | 7x+4=45 | | -12=2(5x-1) | | 21x+15=15 | | -w-2=42 | | 0=x^2+6x-8 | | 6a+2=-a+30 | | (xy)(x^2y)(x^2y)(x^2y)(x^2y)=0 | | 1x+4y=168 | | 21x+5=15 | | x^2-4x-37=0 | | 3x^2+9x-2=-4 | | (xy)(x^2y)(xy)(x^2y)(xy)(x^2y)(xy)(x^2y)=0 | | 3x-5x=8-9 | | log*5(-6-2x)=2 | | (x^2D^2-4xD+6I)y=C | | (xy)(x^2y)(xy)(x^2y)(xy)(x^2y)=0 | | 15y+4=24 | | (5y+6)-(3y+4y)=10 | | a+4=-5a+5 | | 2.7x=0 | | -4b-5=10 | | z^3+3z^2+3z+1=0 | | -5(2y-6)-y=-3(y-3) | | n^2=3n+10 | | (x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)=0 | | 28x^8+16x^3-20x^6+12= | | 9x+11= | | 0.8x=-1.2y | | 90+0.60m=60+0.80m | | 4a+2=3b+5 | | 7x-2y=-2 |

Equations solver categories